Paciente de sexo masculino de 59 años de edad con hemorragia digestiva alta - Sánchez Blum, Kenia Belén (2018)
Upper gastrointestinal bleeding is any loss of blood from the digestive tract between the esophageal sphincter and the treitz angle can be manifested by the presence of hematemesis melenas and sometimes hematochezia, sometimes occurs more in male patients than female, its intensity and frequency depend on many risk factors such as age, presence of concomitant diseases and the use of gastrolesive drugs, the main causes of upper gastrointestinal bleeding are: peptic ulcers representing 50% of cases, esophagitis, gastritis, duodenitis, esophageal varices, tears of marllory wess, digestive tumors, which makes it a medical-surgical emergency of hospital admission. The purpose of this case study is to demonstrate and apply the process of nursing care that should be offered to patients with upper gastrointestinal bleeding based on the theoretical basis of nursing and above all on the principles of nursing such as: humanism, providing an attention with quality, warmth and efficiency. This will allow us to detect and prioritize the needs and / or health problems that the patient presents through the timely identification of nursing diagnoses and the application of nursing care in an integral manner, thus achieving their early recovery and health welfare. This case study is focused on raising the level of knowledge of society in order to reduce the rate of patients with upper gastrointestinal bleeding due to some of the causes or associated diseases mentioned above